2015
DOI: 10.1155/2015/248760
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Students Acquisition of IT Knowledge and Its Implication on M‐Learning

Abstract: The boom in mobile technology has seen a dramatic rise in its usage. This has led to usage of mobiles even in the academic context for further learning. Although the advantages of m-learning (mobile learning) are visible, studies are required to address the aspects that shape its virtual expectations. The acceptance of mobile technology relies mostly on how the students feel about mobile technology fitting into their requirements. Yet, in spite of the significance in the potential of m-learning, research studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
4
1
1
Order By: Relevance
“…The findings of this research do not support those of previous studies (1,(29)(30)(31)(32)(33)(34)(35)(36)(37). Qualitative analysis results generally confirmed this finding.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this research do not support those of previous studies (1,(29)(30)(31)(32)(33)(34)(35)(36)(37). Qualitative analysis results generally confirmed this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Lin et al (28), learners are more affected by their own classmates than their teachers and will use a mobile device if they have their friends' approval. Previous research has revealed that social influence might affect students' intention to use mobile devices (29,30), and it affects individuals' intention to use technology (1,31,32). According to Venkatesh et al (18), social factors do not influence users in a voluntary context; however, they influence users who are in their first stages of experiencing new devices and those who are working in a mandatory context.…”
Section: Social Influencementioning
confidence: 99%
“…Both advanced information technology expertise and sophisticated mobile skills are strongly correlated with strong fundamental technological abilities. Furthermore, the model determines that individuals' impression of and willingness to adopt m-learning is not significantly affected by their level of basic information technology expertise [19]. The results indicate that m-learning was more likely to be adopted and used by students who are highly proficient in a variety of core information technology tasks.…”
Section: Results Analysis and Discussionmentioning
confidence: 94%
“…MUP is the degree of expertise in using modern-day cell phones. As explained by the previous research, IT proficiency and its current understanding impacts the adoption of mobile phones in learning a system or technology (Balavivekanandhan and Arulchelvan, 2015). Proficiency is considered a vital aspect of technology adoption.…”
Section: Results Demonstrabilitymentioning
confidence: 99%